Creating Social Value: Unveiling Stakeholder Commitments Dynamics in Malaysian Social Enterprise - Abdul Rasit, Zarinah; Mohd Jamil, Muthyaah; Ismail, Aida Hazlin; Salleh, Sharmila Mohamed; Razi, Nur Fadzlina Mahamad; Rasit, Zarinah Abdul (Business and Economic Research, 2024)
Social enterprise represents a convergence of profit-driven organisational structures committed to fostering social impacts, such as expanding employment opportunities or supporting single parents in income generation. This study delves into the depth of stakeholder commitment towards social enterprise initiatives in Malaysia. Employing an interpretative case study methodology, the research utilises multifaceted approaches, including interviews, on-site visits, program observation, and financial statement analysis focusing on a social enterprise entity, Rose Sdn. Bhd. (RSB). The thematic analysis serves as the lens through which commitment dynamics within the social enterprises are explored, drawing upon the dimensions of affective, normative, and continuance commitment within the organisational commitment framework. The research highlights the profound commitment of RSB’s founder to its establishment, driven by personal experiences that instill a profound sense of purpose. The study underscores the pivotal role of the work environment and income opportunities in fostering continual commitment among employees. The conducive atmosphere within RSB fosters dedication and a sense of belonging among its workforce, enhancing the organisation’s sustainability and social impact. By creating a genuine and supportive learning environment, trainers strengthen the bonds between individuals and the organisation, reinforcing their commitment to its objectives. The sincerity of trainers is pivotal in nurturing normative commitment among program participants. Additionally, this research emphasises the critical importance of stakeholder commitment in driving the success and sustainability of social enterprises. Close stakeholder engagement emerges as a core strategy for ensuring the sustainability and efficacy of social enterprise initiatives. By exploring commitment dynamics within social enterprise contexts, this study significantly enriches theoretical understanding in the field.